Microrganismos em solos de Vitis labrusca L. e prospecção de um isolado de Paenarthobacter como promotor de crescimento de plantas - Gayger, Ana Luisa (2021)
The phyllosphere of the vine harbors yeasts, filamentous fungi and bacteria that modulate plant health and the growth and production of grapes. These microorganisms can come from the soil of the vine from the air, from precipitation, transported by vector animals (bees, insects and birds. The diversity and bacterial composition of the soil are associated with the geographic location of the vineyard also due to influences belonging to the physical properties linked to the soil, such as texture, pH, temperature, moisture, carbon and nitrogen reserves. Well-defined manipulation of microbial communities contributes to improving plant growth and production and also maintaining soil fertility, an indispensable component of sustainable agriculture, the present study sought to (i) evaluate the microbiota of Vitis Labrusca L. areas from spatial and temporal variations and (ii) select and identify a microorganism with potential to promote plant growth. at c five points (on the four vertices and in the center) in the layer from 0 to 10 cm using t mug rack with a capacity of 100 cm³, thus prior to soil composites. Chemical analysis of soil and isolation of microorganisms on potato dextrose agar (BDA) and Mueller-Hinton agar (MH) were performed. From the microorganisms obtained, the most abundant, predominant, fast-growing isolate with the greatest capacity for long-term survival (6 months) at low temperature (4ºC) was selected. The bacterial isolate A1 was identified as Paenarthrobacter by analyzing the sequence of the 16S rDNA gene region. Prospective tests included: phosphorus solubilization, zinc solubilization, in vitro phytopathogenic fungus inhibition capacity, germination capacity in corn and soybean seeds, experiments in pots with corn and soybean. From vine cultivation soil samples with different years of existence and from a native area, Paenarthrobacter A1 was isolated and identified. This microorganism predominated in all samples evaluated, being more frequent in the area of a 120-year cultivation. The prospected microorganism has potential as a plant growth-promoting bacterium as it is able to solubilize phosphate and zinc, promote the increase in aerial part fresh mass (MFPA), aerial part dry mass (MSPA), total dry mass (MST) and height of the soybean and corn plant and the increase in root fresh mass (MFR) and root dry mass (MSR) for corn.